Kill three birds with one stone: Mitochondria-localized tea saponin derived carbon dots with AIE properties for stable detection of HSA and extremely acidic pH. (30th March 2023) - Zhang, Shengtao; Li, Bin; Zhou, Jieyu; Shi, Jiayi; He, Zhongjing; Zhao, Yumin; Li, Yan; Shen, Yehua; Zhang, Yongmin; Wu, Shaoping
Graphical abstract: Highlights: Providing a new way for green and high-value applications of tea saponin. We used TS as raw material to synthesize novel carbon dots with AIE properties. Stably HSA detection was ideally achieved using TS-CDs. TS-CDs was used for ratiometric detecting pH in extremely acidic conditions. Mitochondria-localized and HSA imaging at cellular levels can be realized. Abstract: In this work, tea saponin (TS) which is indispensable in Camellia oleifera industry was used to synthesize a class of hydrophobic carbon dots (TS-CDs) with aggregation-induced emission (AIE) properties. A new fluorescent sensing platform based on AIE and non-modified TS-CDs for the detection of human serum albumin (HSA) and pH was developed, respectively. Interestingly, the developed platform is capable of ratiometric detecting extremely acidic pH in the range of 0.2–1.8 linearly (R 2  = 0.9959) due to protonation-deprotonation. Meanwhile, TS-CDs exhibited well stability toward HSA detection over a wide linear range (0–180 μM), long-term (48 h), and wide pH range (2–13). Furthermore, TS-CDs was utilized to localize to mitochondria and detect HSA in living cells, demonstrating its promising perspective in biosensing applications. This work may pave a novel avenue for high value-added utilization in the extraction process of extracting camellia oil for food woody oil.